Pengaruh Inovasi Produk, Brand Image, dan Kualitas Pelayanan terhadap Keputusan Pembelian pada GTT Pusat Oleh-Oleh Kediri - Vianita, Rani; Hidayati, Nur; Zamzam, Nurali Agus Najibul (Fakultas Ekonomi Universitas Samudra, 2025)
The purpose of this study was to determine how the perceptions of customers of the GTT Kediri Oleh-Oleh Center on product innovation, brand image, and service quality on purchasing decisions. A quantitative research strategy was used in this study. A combination of non-probability sampling methods, including accidental sampling and snowball sampling, and Lemeshow's formula were used to conduct the sampling. Using questionnaires as the data collection approach, this study surveyed 96 respondents. Multiple linear regression tests were used as part of the data analysis approach in the statistical tool IBM SPSS Statistics 25 for Windows. Among the factors that influence consumers' final decision to purchase, this study found that product innovation, brand image, and service quality are all important and work together to influence consumer choice.